Teaching practice in Youth and Adult Education: Reflections from a supervised internship in Biological Sciences (Research, Society and Development, 2025)
The present article aims to report and analyze the experiences developed during the Supervised Internship II, carried out at Escolas Municipais Reunidas Castro Alves, located in the municipality of Jiquiriçá, in the state of Bahia (BA), with a class from the Youth and Adult Education Program (EJA), stage VI B. The internship, totaling 100 hours, involved classroom observation, lesson instruction, and the development of pedagogical activities focused on the food chain and human body systems. The methodological approach is qualitative, based on experience reporting and critical reflection. The results indicate greater student engagement when the content is connected to their daily lives and when visual resources and hands-on activities are employed. They also highlight the need for pedagogical adaptations for students who are still in the literacy process. Teacher supervision and collaborative work proved fundamental for improving teaching strategies. It is concluded that the internship in EJA contributes to the consolidation of teaching competencies, emphasizing methodological flexibility, affective mediation, and reflective practice as key elements for inclusive and transformative teaching.